When the Underdog Positioning Backfires! The Effects of Ethical Transgressions on Attitudes Toward Underdog Brands - Kim, Yaeri; Park, Kiwan (Frontiers in Psychology, 2020)
This research investigates the novel link between consumers’ support for underdog brands and their ethical expectations of such brands, and finds that the underdog brand positioning may not always be beneficial. Rather, we argue that the identification-based supporting motivation for underdog brands may backfire when the accompanying specific moral expectation is not satisfied. Study 1 demonstrates that the underdog brand falls into an ethical trap in which consumers judge the brand more harshly when ethical transgressions are committed. In Study 2, the psychological underlying mechanism for this ethical underdog trap effect is proved to be perceived betrayal. In Study 3, a boundary condition, community-related (versus autonomy-related) transgressions, is explored. In Study 4, the three types of transgressions (autonomy, community, and functional) and the mediating effects of perceived betrayal are tested in integrated research design. Finally, theoretical and managerial implications are discussed, followed by conclusions.